(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Most of the electronic industry companies in the Iraqi environment, in general, and the electronic industry companies for television products, in particular, need help measuring the cost of television products according to objective foundations. From this standpoint, the current research aims to apply strategic cost management techniques in electronic industry companies after studying the company’s reality and selecting a product. TV Model 43 LED 01-53, and based on the field visit and company data for the year 2016, the research reached several conclusions, the most important of which is that strategic cost management techniques are among the methods that influence when determining customer value after using them to measure the cost of the TV product in the Electronic Industries Company. The research reached several recommendations, the most important of which is determining the customer’s value by selecting the TV product’s net profit after measuring its cost using strategic cost management techniques in the Electronic Industries Company.